Enhanced cooling capacities of ferroelectric materials at morphotropic phase boundaries - Chukka, Rami (2014)
The electrocaloric properties of PbZr0.52Ti0.48O3(PZT) epitaxial films and 0.7Pb(Mg1/3Nb2/3)O3-0.3PbTiO3 (0.7PMN-0.3PT) single crystals are measured and demonstrated enhanced low temperature refrigeration at morphotropic phase boundary compositions. The results reveal large adiabatic cooling figures in ~260nm PZT films (11 K in 15 V) and 200μm thick 0.7PMN-0.3PT single crystals (2.7 K in 240 V) at Curie transition temperatures and secondary cooling peaks at lower temperatures, near critical points. This is a very useful aspect of ferroelectric cooling elements to attain effective cooling over wide range of working temperatures in solid-state devices.